ON THE DEVELOPMENT AND IMPLEMENTATION OF ENGLISH LANGUAGE PLACEMENT, ACHIEVEMENT AND PROFICIENCY TESTS - Voronova, Ye.; Воронова, Є. М.; Воронова, Е. М. (Харьковский национальный автомобильно-дорожный университет, 2015)
The article deals with the description of three types of English language tests: namely placement, achievement and proficiency ones. Attention is given to different approaches to testing which makes it possible to simulate real life situations.
РОЗРОБКА ТА ІМПЛЕМЕНТАЦІЯ СТАРТОВИХ, КОНТРОЛЬНИХ ТЕСТІВ І ТЕСТІВ ЗА ФАХОМ
РАЗРАБОТКА И ИМПЛЕМЕНТАЦИЯ СТАРТОВЫХ, КОНТРОЛЬНЫХ ТЕСТОВ И ТЕСТОВ ПО СПЕЦИАЛЬНОСТИ
Keywords: approach; testing; communication; situations; simulation; підхід; тестування; спілкування; ситуації; моделювання; подход; тестирование; общение; ситуации; моделирование; 811.111:001.891.5=111